Image‐Guided Magnetic Thermoseed Navigation and Tumor Ablation Using a Magnetic Resonance Imaging System. Issue 12 (2nd February 2022) - Baker, Rebecca R.; Payne, Christopher; Yu, Yichao; Mohseni, Matin; Connell, John J.; Lin, Fangyu; Harrison, Ian F.; Southern, Paul; Rudrapatna, Umesh S.; Stuckey, Daniel J.; Kalber, Tammy L.; Siow, Bernard; et al.
Abstract: Medical therapies achieve their control at expense to the patient in the form of a range of toxicities, which incur costs and diminish quality of life. Magnetic resonance navigation is an emergent technique that enables image‐guided remote‐control of magnetically labeled therapies and devices in the body, using a magnetic resonance imaging (MRI) system. Minimally INvasive IMage‐guided Ablation (MINIMA), a novel, minimally invasive, MRI‐guided ablation technique, which has the potential to avoid traditional toxicities, is presented. It comprises a thermoseed navigated to a target site using magnetic propulsion gradients generated by an MRI scanner, before inducing localized cell death using an MR‐compatible thermoablative device. The authors demonstrate precise thermoseed imaging and navigation through brain tissue using an MRI system (0.3 mm), and they perform thermoablation in vitro and in vivo within subcutaneous tumors, with the focal ablation volume finely controlled by heating duration. MINIMA is a novel theranostic platform, combining imaging, navigation, and heating to deliver diagnosis and therapy in a single device. Abstract : Minimally invasive image‐guided ablation is a novel therapy that uses a magnetic resonance imaging (MRI) scanner to deliver precise focal ablation therapy. A ferromagnetic thermoseed is navigated to the target using the magnetic field gradients generated by the MRI scanner and then heated using an MR‐compatible radiofrequency coil to deliver localized thermoablation.